2021
DOI: 10.5534/wjmh.190135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Benign Prostatic Hyperplasia and/or Prostatitis on the Risk of Prostate Cancer in Korean Patients

Abstract: Prostate cancer (PCa) is the second most common cancer and the fifth leading cause of cancer-related death worldwide [1]. In Korea, the incidence of PCa is increasing rapidly [2]. Currently, there are established risk factors for diagnosing PCa [3]. Family history, increased age, and ethnicity are established risk factors for PCa diagnosis, while among many other potential risk factors, benign prostatic hyperplasia (BPH) andPurpose: We evaluated the impact of benign prostatic hyperplasia (BPH) and prostatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…There are several series that traced the clinical implication of PSA decrease following BPH/ LUTS medication, including alpha-blockers and antibiotics. Tubaro et al 12 A decrease in PSA in suspicious levels was also reported in studies that administered antibiotics 14,15 because subclinical inflammation of the prostate could elevate serum PSA in an asymptomatic way.…”
Section: Discussionmentioning
confidence: 82%
“…There are several series that traced the clinical implication of PSA decrease following BPH/ LUTS medication, including alpha-blockers and antibiotics. Tubaro et al 12 A decrease in PSA in suspicious levels was also reported in studies that administered antibiotics 14,15 because subclinical inflammation of the prostate could elevate serum PSA in an asymptomatic way.…”
Section: Discussionmentioning
confidence: 82%
“…Kim SH reported the incidence of PCa in prostatitis was 1.64%. Furthermore, the patients with prostatitis had a higher risk of PCa than the patients without prostatitis (12). Chronic asymptomatic prostatitis was detected in 31% patients with PCa, and there was a positive correlation between the inflammation aggressiveness grade and urological pathology grades.…”
Section: Original Articlementioning
confidence: 91%
“…The chronic nature of the disease can lead to feelings of tension, anxiety, and depression, affecting both the quality of life and disease recovery for patients. [ 3 , 4 ] Although complete cure for BPH is currently unachievable, clinical treatment options exist that significantly improve symptoms in affected individuals. Additionally, providing appropriate nursing measures and health guidance during the treatment process have positive implications for alleviating patient conditions and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%